Stanisław Barańczak: Between autonomy and support - Szymanska, K (Frank & Timme, 2016)
Stanisław Barańczak (1946-2014), a leading poet of the Polish ‘New Wave’ formation, dissident intellectual, prolific translator and, from the early 1980s until his recent death, an émigré and professor at Harvard University, remains one of the most prominent translation critics and literary figures in Poland. This article attempts to revisit his first theoretical paper on literary translation entitled ‘Przekład jako “samoistny” i “związany” obiekt interpretacji’ [The Translation as a 'Self-sufficient' and 'Integrated' Object of Interpretation] ([1972] 1974) and to present his early scholarship within the Structuralist framework of literary communication. In academic criticism this particular text has generally been misinterpreted: it has usually been deemed analytically unhelpful and believed to reiterate some of the clichés of Translation Studies. This article will attempt to discard those oversimplified interpretations by establishing a bridge between Barańczak’s theoretical claims and his own translation practice. The concept of translation as a “self-sufficient” and “integrated” object of interpretation will be discussed with special reference to the way Barańczak himself later constructed and published his own literary translations, his ethical approach to autonomy and support in translation, as well as the general intellectual and literary context of that time.